Bitlis Bibliophil Association and One-Book Project - Hakan Yücel (Türk Kütüphaneciliği)
The article deals with Bitlis Bibliophil Association and One-Book Project which was established in January of the current year by a group of volunteer including several professions such as students, librarians, sociologists, engineers, civil cervants, teachers, bankers, poets, jorunalists, accountants.